Navigating a changing world economy: ASEAN, the People's Republic of China, and India - Peter A. Petri; Fan Zhai (Asian Development Bank Institute (ADBI), 2013)
Most projections envision continued rapid growth in the members of the Association of Southeast Asian Nations (ASEAN), the People's Republic of China (PRC), and India (collectively, ACI) over the next two decades. By 2030, they could quadruple their output, virtually eliminate extreme poverty, and dramatically transform the lives of their more than 3 billion citizens. The impact will be felt across the world. This study - a background paper to an Asian Development Bank report - used a Computable General Equilibrium model to examine the likely effects of the region's growth on trade, resources and the environment, as well as the implications of the many risks the region's growth path faces from its internal and external environment.
Keywords: F02; F13; F33; F53; 330; asean; prc; india; world economy; aci; great transformation; growth engines; Wirtschaftswachstum; Großmacht; Weltwirtschaftsordnung; ASEAN-Staaten; China; Indien